Effect of Calcium Lactate, Sodium Diacetate and Sodium Chloride Mixture on the Microbiological, Chemical and Sensory Properties of Chicken Nuggets Stored in Refrigeration and under Modified Atmospheres - Yavas, E.; Bilgin, B. (International Journal of Poultry Science, 2009)
This study was conducted to assess the effects of 0.5% Preservative Mixture (PM) containing calcium lactate (40%), sodium diacetate (40%) and sodium chloride (20%) on the microbiological, chemical and sensory quality of chicken meat nuggets stored at 4±2oC and under Modified Atmosphere Packaging (MAP). There were two experimental groups of samples, namely control and PM-treated. The results showed that the PM-treated nugget samples had significantly (P<0.05) lower total bacterial count (TAB), coliform, Peroxide Value (PV) and Free Fatty Acids (FFA). At the same time, PM-treated nugget samples markedly higher scores for sensory evaluation such as appearance, texture, taste, odour and totally.